Fisiopatologia dell’ipertensione portale e della ritenzione idrosalina nella cirrosi - Giovanni Garini; Marco Delsante; Francesco Iannuzzella (Recenti Progressi in Medicina, 2011)
Portal hypertension is caused by an increased resistance to portal outflow and an increased portal blood inflow. Portal hypertension is associated with an abnormal distribution of the blood volume, which is increased in the splanchnic territory and reduced in the non-splanchnic compartments. The relative underfilling of the arterial circulation is responsible for the sodium and water retention, which is a consequence of the baroceptor-mediated activation of vasoconstrictor and antinatriuretic factors triggered to restore circulatory integrity.